A Randomized Study of Standard versus Double dose Oseltamivir for Treating Influenza in the Community. Issue 7 (October 2015) - Dixit, Rashmi; Khandaker, Gulam; Hay, Peter; McPhie, Kenneth; Taylor, Janette; Rashid, Harunor; Heron, Leon; Dwyer, Dominic; Booy, Robert
Background: The neuraminidase inhibitors are the treatment of choice for influenza virus infection. Oseltamivir-resistant (OsR) strains of influenza A(H1N1)pdm09 are described, but the effect of higher dose oseltamivir on efficacy, safety and emergence of resistance has not been addressed in the developed setting in outpatients. The objectives of the study were to compare standard dose (SD) versus double dose (DD) oseltamivir regimens for frequency of detecting OsR influenza virus, clinical disease resolution, virological clearance and adverse events. Methods: This was an unblinded randomized controlled trial of community-based patients with confirmed influenza. Participants were randomized to a 5-day regimen of either SD or DD oseltamivir. Results: Of 52 participants (aged 4.8–54.8 years), 25 received SD and 27 DD oseltamivir. Clinical resolution did not differ by dosing regimen ( P =0.43); neither did virological clearance differ for either influenza A ( P =0.20) or B ( P =0.70). Adverse events, predominantly gastrointestinal, were greater with DD than SD ( P =0.04). One OsR strain was detected prior to treatment and two individuals developed OsR strains during treatment, one each on SD and DD. Those with OsR strains did not appear to have a different clinical course. Conclusions: DD oseltamivir did not appear to provide a clinical or virological advantage, nor reduce the emergence of oseltamivir resistance, but our study was underpowered. Adverse events occurred more frequently on DD compared to SD oseltamivir.